THE IMPLICATIONS OF BEHAVIORISM, COGNITIVISM, AND CONSTRUCTIVISM LEARNING THEORIES IN THE DEVELOPMENT OF KURIKULUM MERDEKA ISLAMIC RELIGIOUS EDUCATION (PAI): A SYSTEMATIC LITERATURE REVIEW - Qiqi Yuliati Zaqiah; Eri Hadiana; Agus Hidayat; Ujang Koswara; Hamdan Maulana; Naufal Abdillah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This Systematic Literature Review (SLR) analyzes the integration and contemporary implications of Behaviorism, Cognitivism, and Constructivism learning theories within the framework of the Kurikulum Merdeka (Independent Curriculum) in Islamic Religious Education (PAI) in Indonesia. The SLR adhered to the PRISMA-Lite protocol, examining 25 studies published between 2020 and 2025 focusing on the functional relationship between learning theories and the Kurikulum Merdeka PAI. Thematic synthesis was employed to categorize the role of each theory across the cognitive, affective, and psychomotor domains. The implementation of PAI is characterized by functional eclecticism. Behaviorism remains essential for repetitive practical skills (shalat and wudu mastery). Cognitivism acts as a crucial bridge for processing complex conceptual knowledge (Fiqh, Aqidah) through tools like advanced organizers. Crucially, Constructivism serves as the central philosophical core, utilized in Project-Based Learning (P5) to foster critical character, religious moderation, and contextual application of Islamic values. The findings highlight a necessary pedagogical shift in PAI from a purely doctrinal approach to an adaptive, student-centered model. Successful transformation requires targeted professional development for PAI teachers in facilitating constructive and cognitive strategies to meet the holistic demands of the curriculum